Study On The Mechanical Performance Of Normal Concrete Due To Inclusion Of PVA Fibers And Silica Fume - Tidan, Deirdre Rinai (Universiti Teknologi PETRONAS, 2020)
Concrete is a component in the construction industry that is perpetual and resolute since the beginning. Modifications are done to improve the properties of concrete, but concrete is yet to be replaced in the practices of construction. One example of modifications will be the inclusion of cement replacement material such as fly ash, silica fume, fibers and more. These researches are done to enhance and improve the properties of the concrete. That being the focus of the research, PVA fiber and silica fume are two components that are widely used in concrete researches due to their proven abilities in past researches to increase the properties of the concrete. The gap in the researches was found, where the combination of PVA fiber and silica fume on the normal concrete mixture is not done yet, and therefore addressed in this study.